2017
DOI: 10.1021/jacs.7b03887
|View full text |Cite
|
Sign up to set email alerts
|

C–H Alkenylation of Heteroarenes: Mechanism, Rate, and Selectivity Changes Enabled by Thioether Ligands

Abstract: Thioether ancillary ligands have been identified that can greatly accelerate the C-H alkenylation of O-, S-, and N-heteroarenes. Kinetic data suggest thioether-Pd-catalyzed reactions can be as much as 800× faster than classic ligandless systems. Furthermore, mechanistic studies revealed C-H bond cleavage as the turnover-limiting step, and that rate acceleration upon thioether coordination is correlated to a change from a neutral to a cationic pathway for this key step. The formation of a cationic, low-coordina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
109
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(116 citation statements)
references
References 88 publications
(54 reference statements)
7
109
0
Order By: Relevance
“…[71b] Kinetic studies indicated the presence of 56 led to an acceleration of turnover-limiting activation of the heteroarene substrate by standard CMD. DFT calculations on the two competing standard CMD pathways involving the typically proposed intermediate, ( t Bu 3 P)Pd(Ph) (k 2 -OAc) (54), and the in situ generated metallocycle 56 supported the latter as being more reactive by ΔΔG � = 6 kcal/ mol. Based on these observations, a catalytic process was proposed in which the palladacycle promotes standard CMD to generate 57 followed by Pd-to-Pd transmetalation with the OA complex (53/54) to give diarylÀ Pd species 55 that generates product through CÀ C reductive elimination (Figure 28).…”
Section: Multi-metallic Pathways For Catalytic Processes Involving Ammentioning
confidence: 93%
See 3 more Smart Citations
“…[71b] Kinetic studies indicated the presence of 56 led to an acceleration of turnover-limiting activation of the heteroarene substrate by standard CMD. DFT calculations on the two competing standard CMD pathways involving the typically proposed intermediate, ( t Bu 3 P)Pd(Ph) (k 2 -OAc) (54), and the in situ generated metallocycle 56 supported the latter as being more reactive by ΔΔG � = 6 kcal/ mol. Based on these observations, a catalytic process was proposed in which the palladacycle promotes standard CMD to generate 57 followed by Pd-to-Pd transmetalation with the OA complex (53/54) to give diarylÀ Pd species 55 that generates product through CÀ C reductive elimination (Figure 28).…”
Section: Multi-metallic Pathways For Catalytic Processes Involving Ammentioning
confidence: 93%
“…The highest selectivity was observed for Pd catalysts coordinated by anionic thioethers L2 or L3, which are particularly reactive toward CÀ H alkenylation with electronrich heteroarenes. [54] This switch in substrate preference could be indicative of a change in the nature of the transition state of CÀ H cleavage; while tempting to attribute the electrophilic reactivity in the CÀ H alkenylation reactions to a step-wise S E Ar type pathway, it was shown for the thioetherÀ Pd cases that CÀ H cleavage is turnover-limiting. It should be noted that the turnover-limiting step of CÀ H alkenylation has not been established for cases employing pyridine-or DAF-coordinated Pd(OAc) 2 .…”
Section: Electrophilic Thioetherà Pd(ii) Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…[18] In the studies on the thioether ligand-promoted CÀ H alkenylation of heteroarenes, Carrow and co-workers also disclosed feasible aerobic examples of indole functionalization (Scheme 7, conditions D). [19] For selective indole C2 alkenylation, the strategy of directing CÀ H activation could be used. In this regard, earlier works focused on the palladium-catalyzed oxidative Heck reactions, in which Cu(OAc) 2 was generally used as the terminal electron acceptor.…”
Section: Indole Alkenylationmentioning
confidence: 99%